Functional assessment of non-coding regulatory variants in familial breast cancer - O'BRIEN, CAROL (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2020)
Breast cancer is the most common cancer in Irish women, with almost 3,000 cases diagnosed every year. It often runs in families, and some women inherit a greater risk of developing the disease. Landmark studies on these families led to the discovery of breast cancer susceptibility genes such as BRCA1 and BRCA2. However, mutations in BRCA1, BRCA2 and other susceptibility genes are only detected in ~25% of women with familial breast cancer. Despite extensive efforts to uncover the genetic susceptibility to breast cancer, much of the heritability remains unexplained. To address this issue, we hypothesised that pathogenic germline mutations may be located in the non-protein-coding, regulatory regions of the genome. We carried out targeted sequencing of promoter and candidate enhancer regions of 143 cancer-associated genes in 104 high-risk non-BRCA1/2 Irish familial breast cancer cases and 101 geographically-matched controls. We found that case-enriched non-coding variants were capable of disrupting transcription in a luciferase reporter assay and that they are predicted to disrupt transcription factor binding sites. Furthermore, we show that deletion of an enhancer region containing a rare case-enriched single nucleotide variant (SNV), which is in proximity to PIK3CA, appears to result in a decrease in ZMAT3 expression. Our results demonstrate that interrogation of the non-protein-coding region in proximity to cancer-associated genes is a worthwhile endeavour. We anticipate this study to be a starting point for yet more sophisticated modelling of the effect of the SNV through the generation of isogenic cell lines containing just the single nucleotide mutated in patients. We hope that this project will make an important contribution to both our knowledge about the genetic causes of breast cancer, as well as adding to the discussion surrounding the functional validation of non-coding variants.
APPROVED
Keywords: Breast cancer; Non-coding variants; Genetics